PENYULUHAN PENCEGAHAN PENYAKIT INFEKSI MIKROORGANISME PADA SANTRIWAN DAN SANTRIWATI PONDOK PESANTREN KYAI MAROGAN PALEMBANG : PENYULUHAN PENCEGAHAN PENYAKIT INFEKSI MIKROORGANISME PADA SANTRIWAN DAN SANTRIWATI PONDOK PESANTREN KYAI MAROGAN PALEMBANG (STIKes Mitra Keluarga, 2022)
Introduction: Infection prevention and control is the application of microbiology in clinical practice and its success depends on the theoretical knowledge of microbiology that underlies safe clinical practice. Infectious diseases are still one of the health problems in the world, including Indonesia. Judging from the origin or acquisition of infection can come from the community (Community Acquired Infection) or come from the environment. Objective: to increase knowledge about infection prevention and control application of microbiology in clinical practice and its success. Solution: Conduct infection prevention and control counseling to students who are queuing and at the Kyai Marogan Islamic boarding school in Palembang. Time : Held on Thursday, August 26, 2021, attended by 96 students and students, with 3 lecturers and 3 students as implementers. Results: There was an increase in the understanding of students and female students (100%) after counseling on infection prevention and control to students and female students queuing at the Kyai Marogan Islamic Boarding School in Palembang. Suggestion: To always instill the belief that cleanliness is part of our faith, be open and respectful to each other to improve personal and environmental hygiene.